Benefit of regional anaesthesia on postoperative pain following mastectomy: the influence of catastrophising. (August 2019) - Zinboonyahgoon, Nantthasorn; Vlassakov, Kamen; Lirk, Philipp; Spivey, Tara; King, Tari; Dominici, Laura; Golshan, Mehra; Strichartz, Gary; Edwards, Robert; Schreiber, Kristin
Abstract: Background: Previous studies suggest that truncal regional anaesthesia (TRA), including techniques such as paravertebral block, may contribute significantly to analgesia after mastectomy. However, the severity and impact of postoperative pain varies markedly amongst individuals, making the identification of patients who would benefit most from TRA a potentially important step toward personalised perioperative care. Methods: In this prospective observational study, mastectomy patients ( n =122) were recruited and systematically assessed for psychosocial characteristics including pain catastrophising before surgery, and either received preoperative TRA ( n =57) or no block ( n =65). Results: Age, baseline pain, and psychosocial traits did not differ between these groups. TRA was associated with lower overall pain scores and opioid consumption perioperatively, with a larger proportion of patients without block (50% vs 28%) reporting moderate-severe pain (more than three/10) on the day of surgery. Mixed model analysis of variance revealed a significant interaction between catastrophising and TRA, such that amongst patients with high baseline catastrophising, TRA was associated with substantially lower pain severity score (58% lower), while amongst patients with low baseline catastrophising, TRA was associated with only 18% lower pain severity. At 2 weeks, this interaction between baseline catastrophising and TRA was also observed when examining surgical pain burden, with higher baseline catastrophising patients who had received TRA reporting lower pain and less frequent opioid use (40% vs 70% of patients). Conclusions: TRA provided immediate analgesic benefit for patients undergoing mastectomy on the day of surgery, but this effect appeared more pronounced and sustained amongst patients with higher baseline catastrophising. Clinical trial registration: NCT 02329574.